Tomada de decisão em investimentos na produção de oleaginosas para o setor do biodiesel, com foco na pequena e média empresa: uma abordagem de análises discriminantes e fatorial - Almeida, Luciana Gondim Rocha de (2008)
Brazilian median and small biooil country producers working on the Biodiesel production chain normally need the aid of public policies to guide the sector to sustainable development with social inclusion. Those policies are necessary to avoid the concentration of production in few large producers, as it has happened with sugar cane ethanol supply chain in Brazil. So, the aim of the present research work is to identify which are the key-variables and their relative importance to support public policies aiming the increase in agricultural production in Brazilian median and small biooil country producers’ sector. Data are elicited from a sample of 162 small and median producers in Ceará, a poor Brazilian county in its northeastern region, as well as from experts in Biodiesel agricultural input practices. A questionnaire was applied involving 54 variables considered important, according with literature research, in terms of their impacts in biooil inputs production. The methodology applied to face the study problem uses both discriminant and factorial analysis to identify similarities among respondents and to analyze the main key-variables in their decision taking process. Main results of the present work show that are no statistically significant differences in responses of both groups researched. Factorial analysis application revealed high importance, to the individuals sampled, of variables related to associative producers’ clusters as well as to the support they may have from governmental authorities, relating to technical aspects or to personnel training in the focused sector. Familiar agriculture structured systems are based in community practices and in interaction with their environment. They also use to valorize availability of logistics equipments, basic services (educational and health facilities) and credit. Finally, many actions are put forward to support governmental policies aiming the development of the Biodiesel production sector in the County of Ceará.